Pengaruh Role Conflict, Role Ambiguity Dan Beban Kerja Terhadap Kinerja Karyawan Pada PT. SBC Berkah Bersama - Oktavia Friska Diah Palupi; Budi Wahono; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Employee performance is very important for the company. This study aims to analyze the effect of role conflict, role ambiguity and workload on employee performance at PT. SBC Blessing Together. Sampling for this study used the Slovin formula with a population of 200 and resulted in 66 samples of employees. Data collection was done by distributing questionnaires. In this research, the analytical technique used is SPSS. The results showed that there was a negative and significant influence between Role Conflict, Role Ambiguity on Employee Performance and positive and negative influence between Workload on Employee Performance. Keywords: Role Conflict, Role Ambiguity, Workload and Employee Performance